To Swap or Not to Swap? Exploiting Dependency Word Pairs for Reordering in Statistical Machine Translation - Hadiwinoto, Christian; Liu, Yang; Ng, Hwee Tou (Proceedings of the AAAI Conference on Artificial Intelligence, 2016)
Reordering poses a major challenge in machine translation (MT) between two languages with significant differences in word order. In this paper, we present a novel reordering approach utilizing sparse features based on dependency word pairs. Each instance of these features captures whether two words, which are related by a dependency link in the source sentence dependency parse tree, follow the same order or are swapped in the translation output. Experiments on Chinese-to-English translation show a statistically significant improvement of 1.21 BLEU point using our approach, compared to a state-of-the-art statistical MT system that incorporates prior reordering approaches.